CLAUDIO MAGRIS: THE DIALECTICS OF HARMONY AND DISINTEGRATION - Dąbrowski, Mieczysław (Porównania, 2012)
The article is dedicated to the essayistic work of Claudio Magris, a great Italian essayist and researcher of culture in Eastern Europe and the Balkans. Magris’ well-known works such as “Microspaces”, “The Danube” and “Endless travels” constitute the foundation for the discussion. The author of the article extracts important plots in Magris’ works such as nostalgia and melancholy, harmony and disintegration. He carries out an analysis of Magris’ writings by means of referring the above mentioned plots to the world in which the author of “The Danube” sees the roots of the most important in his opinion values of Central Europe. It is a world of the non-existent Austro-Hungarian monarchy from before 1918 shown in the context of the fall of humanism, moral norms and absolute relativism.